From Traditional Assessment to the New Competency-Based Assessment - Mejía Pérez, Omar (2012)
The evaluation of school students has always attempted to estimate the effort, abilities and learning of students. However, at the beginning, evaluation consisted in measuring the progress of the student’s behavior compared to a desirable behavior. Later on, different changes in evaluation benefited the processes addressed to assessing the academic achievement of students and learning itself. Today, the demands of the contemporary society are vast and numerous: students not only require knowledge, they need to develop skills, values and postures. Postmodern education requires individuals to develop different talents and competencies to grow in every way. Therefore, evaluation should respond to such needs promoting an ethical, technical, reliable assessment of the student’s competencies, thus providing more fair and objective, qualitative and quantitative judgments. This dissertation project is the result of a literature review of several authors and the daily work of teachers in the Centros de Educación Media Superior a Distancia [High School Distance Centers] of Morelos, Mexico.